PRODUCTION OF HUPERZINE A BY FUNGAL ENDOPHYTES ASSOCIATED WITH HUPERZIACEAE PLANTS - Ariantari, Ni Putu; Putri, Ni Wayan Prasanthi Swarna (Journal Pharmaceutical Science and Application; Vol 5 No 1 (2023): Journal Pharmaceutical Science and Application (JPSA)DO - 10.24843/JPSA.2023.v05.i01.p06, 2023)
Background: Endophytic fungi are known as a producer of a myriad of bioactive natural products, including those originally produced by the host plants. Huperzine A (Hup A), a lycopodium alkaloid, which was reported as an active acetylcholinesterase inhibitor (AChEI) agent used for the treatment of Alzheimer’s disease, was originally isolated from medicinal Chinese herbs Huperzia serrata. Moreover, various species of endophytic fungi associated with H. serrata and other species within Huperziaceae plants were found capable of producing Hup A, suggesting these microorganisms as promising sources of Hup A. Objective: This review aimed to summarize the evidence of Hup A produced by various endophytic fungi as part of efforts to assess alternative producer of Hup A. Methods: Scientific articles on endophytic fungi producing Hup A published from 2000 until 2022 were screened through scientific databases. Results: Thirty-two endophytic fungal strains belonging to fifteen fungal genera were documented as capable of producing Hup A. These fungal endophytes were isolated from Huperziaceae plants, H. serrata, Phlegmariurus phlegmaria and Phlegmariurus taxifolius. Conclusion: We summarize herein the capability of endophytic fungal strains associated with Huperziaceae plants to produce Hup A, an active AChEI agent, which could be considered as an alternative producer of Hup A on a larger scale. Keywords: Acetylcholinesterase inhibitor (AChEI); Alzheimer’s disease; Fungal endophytes; Huperziaceae; Huperzine A (Hup A).